The Impact of the Independent Curriculum on 21st Century Skills on Grade IV Students of SDN 24 Palu - Herlina, Herlina; Wulandari, Wulandari; Muchdar, Muchdar; Nashrullah, Nashrullah; Nuraini, Nuraini (FKIP - Universitas Riau, 2025)
This study aims to determine the impact of the independent curriculum on 21st century skills in grade IV students of SDN 24 Palu. This study uses a qualitative research approach of phenomenological studies. The subjects in this study are teachers and grade IV students of SDN 24 Palu. The instruments in this study are questionnaires, interviews, observations and documentation. The data collection techniques used were questionnaires, interviews, observations and documentation. Then the collected data is analyzed through the process of data reduction, data presentation and conclusion drawn. The results of the study show that the independent curriculum encourages students to be more active, creative and independent by emphasizing critical thinking, communication, creativity, collaboration, character and citizenship skills so that it has a positive impact on the development of 21st century skills in grade IV students of SDN 24 Palu even though the results of student observation in its application are still low so it needs further improvement. Through various learning methods such as discussions, group assignments, students get used to expressing ideas, making decisions together and working together with their friends. However, the results of teachers' observations on the implementation of the independent curriculum are sufficient so that there is still a need to improve teachers' understanding, learning strategies and support from various parties.